Shigella sonnei and hemolytic uremic syndrome: A case report and literature review. (2017) - Adams, Casey; Vose, Aaron; Edmond, Michael B.; Lyckholm, Laurel
Abstract: Hemolytic uremic syndrome (HUS) is a well-described process that is known to cause severe renal dysfunction, thrombocytopenia, and anemia. HUS is typically associated with toxins (shiga-like and shigella toxin) found in strains of E. coli and Shigella spp[1–3] . We present a case of a 27 year-old man with jaundice, thrombocytopenia, and renal dysfunction who was found to have HUS in the setting of Shigella sonnei infection. Outside of developing countries, cases of HUS related to S. sonnei are largely unreported.